Seeing the content of the mind: enhanced awareness through working memory in patients with visual extinction. - Soto, D; Humphreys, G (2006)
In the present study, we demonstrate that parietal patients with visual extinction show enhanced awareness when there is a match between the current contents of their working memory and the stimuli presented in the visual field. This effect cannot be attributed to automatic bottom-up priming from the presentation of a memory cue, because extinction was reduced only when patients committed the cue to memory, and not when primes were viewed passively or merely identified. The results suggest that reentrant processes, from working memory, modulate awareness.